The Genotoxicity of Acrylamide and Glycidamide in Big Blue Rats - Mei, Nan; McDaniel, Lea P.; Dobrovolsky, Vasily N.; Guo, Xiaoqing; Shaddock, Joseph G.; Mittelstaedt, Roberta A.; Azuma, Mizuo; Shelton, Sharon D.; McGarrity, Lynda J.; Doerge, Daniel R.; Heflich, Robert H. (Toxicological sciences, 2010)
Acrylamide (AA), a mutagen and rodent carcinogen, recently has been detected in fried and baked starchy foods, a finding that has prompted renewed interest in its potential for toxicity in humans. In the present study, we exposed Big Blue rats to the equivalent of ∼5 and 10 mg/kg body weight/day of AA or its epoxide metabolite glycidamide (GA) via the drinking water, an AA treatment regimen comparable to those used to produce cancer in rats. After 2 months of dosing, the rats were euthanized and blood was taken for the micronucleus assay; spleens for the lymphocyte Hprt mutant assay; and liver, thyroid, bone marrow, testis (from males), and mammary gland (females) for the cII mutant assay. Neither AA nor GA increased the frequency of micronucleated reticulocytes. In contrast, both compounds produced small (approximately twofold to threefold above background) but significant increases in lymphocyte Hprt mutant frequency (MF, p < 0.05), with the increases having dose-related linear trends (p < 0.05 to p < 0.001). Neither compound increased the cII MF in testis, mammary gland (tumor target tissues), or liver (nontarget tissue), while both compounds induced weak positive increases in bone marrow (nontarget tissue) and thyroid (target tissue). Although the genotoxicity in tumor target tissue was weak, in combination with the responses in surrogate tissues, the results are consistent with AA being a gene mutagen in the rat via metabolism to GA.